AIR COOL Air-Conditioner Services &Trading Co. / Norafiza Babjan ... [et al.] - Babjan, Norafiza; Abu, Rosmaliza; Abd Aziz, Aishah; Abu Bakar, Azhar; Kamal Ariffin, Noor Hizazmie (2002)
We have decided to choose AIR COOL Air-Conditioner Services and Trading Co. as our business name. The nature of our business is supplying air-conditioner from an established brand, which is Carrier and Top-Aire. Besides that we give services to industrial, commercial and residential. In addition, we also provided installation and maintenance to fulfill consumer's needs and wants. We are operating a partnership form of business. We have five partnerships that are the Board of Directors of the company who contributes capital of the setting up of AIR COOL Air-Conditioner Services and Trading Co. Each of our Board of Directors is holding their own post in the company. The capital that all of the partners contribute is RM 250,000. Each partners contributed RM 50,000 that is 13.3334% each. The balance of the capital, we get from bank loan where the amount is RM 125,000. We are getting the bank loan from Bank Islam Malaysia Berhad. All the partnership has a good qualification in studies. Besides that we also have working experience on related field that make us willing to venture into this type of business. Furthermore, we are hiring experience workers in every department, so that all the matters exist can be handle by experience people. This is to make sure that things are done properly and with productivity, efficiency and consistently.